(untitled) (Foro de Educacion, 2014)
There was a whole network of schools in the University of Salamanca in the 16th century based their existence on training a select group of students and provide the Crown and the Church of men well formed spiritually and intellectually. We address in this study an approach to pedagogy Colegio Menor San Pelayo de Salamanca. The Constitutions and Ceremonies printed in 1637 are the source from which we draw the pedagogy of this educational institution born in the 16th century. This body of law is steeped in a declaration of intentions and pedagogical objectives that schoolchildren had to meet for the sake of his intellectual and religious. Timetables, hierarchy, rules of life, morality and spirituality, everything was regulated for proper community life and training of a class intended to occupy the highest administrative and ecclesiastical dignities in the Modern Age.